Clinical Efficacy of Celecoxib with and without Caffeine versus Ibuprofen for Pain Control following Crown Lengthening Surgery - Jenabian, Niloofar; Moghadamnia, Ali Akbar; Beyraghshamshir, Reza (Journal of Dental School, 2019)
Objective: Non-steroidal anti-inflammatory drugs (NSAIDs) are the most commonly prescribed pain control medications following periodontal surgery. This study aimed to compare the efficacy of three drug regimens namely celecoxib, celecoxib + caffeine and ibuprofen for pain relief following crown lengthening surgery. Methods: This randomized, double blind clinical trial was performed on 45 patients aged 20-60 years requiring crown lengthening of maxillary teeth. The subjects were randomly divided into three groups (n=15) receiving ibuprofen (400mg), celecoxib (200mg) and celecoxib (200mg) + caffeine (30mg). Each patient took one dose of the respective medications 30 minutes prior to surgery. Other doses were prescribed 1, 8, 16 and 24 hours after surgery. Pain scores were recorded using visual analog scale (VAS) at 1, 2, 4, 8, 16, 24 and 48 hours post operation. Results: The mean VAS scores were significantly lower in celecoxib + caffeine group than in celecoxib group at 1 and 2 hours after surgery (H1: 2.33 (1.95) vs. 4.47 (2.56), p=0.026) (H2: 2.47 (1.60) vs. 4.80 (2.40), p=0.009). The pain scores were significantly lower in celecoxib + caffeine group than ibuprofen group at 8, 16 and 24 hours after the procedure (H8: 1.80 (1.21) vs. 3.73 (1.94), p=0.012) (H16: 1.07 (1.03) vs. 2.73 (1.87), p=0.012) (H24: 0.47 (0.64) vs. 1.87 (1.25), p=0.004). No significant difference was found in analgesic efficacy of celecoxib and ibuprofen. Conclusion: The combination of celecoxib + caffeine showed higher efficacy than other medications for pain control following crown lengthening surgery. Caffeine may enhance the analgesic effect of celecoxib.